Nestlé (dis)entangled!. B : braving the Maggi noodle crisis in India - Chaudhri, Vidhi; Kaul, Asha (London : Indian Institute of Management, Ahmedabad, 2022)
On May 21, 2015, the Food and Drug Administration (FDA) ordered Nestlé India to recall Maggi noodles after confirming the presence of high levels of lead and monosodium glutamate in the product. The test was conducted on 29 samples, out of which 15 had tested positive. The media reports shared the findings and detailed the harmful effects of Maggi consumption. As a mark of protest against "unhealthy" food products on the market, hostile consumers began burning packets of Maggi. Nestlé CEO Paul Bulcke read the report on Maggi in India. Recall they must, thought Bulcke, but what would be the aftermath of the recall? Will they be able to get Maggi back on the shelf? Will they ever be able to recapture consumer faith and trust?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Customer relations -- Management -- Case studies; Crisis management -- Case studies